INVESTIGATING PWD REVISIT INTENTION FOR ENTREPRENUERIAL PASTRY COURSE AT SELAYANG COMMUNITY COLLEGE: THE MODERATOR ROLE OF GENDER - Mohd Hyrul Abu Karim; Mohd Khaidir Che Hassan; Azmarita Muhamad Bahari (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
People with disabilities (PWD) empowerment has become a topic of international discussion. Individuals from this population are more likely to be in low-paying jobs and have the lowest prospects for promotion of any group across most industries. It is important to train PWD students to be more confident and to become semi-skilled workers before they enter the workforce. In 2020, there is no course conducted at Selayang Community College (KKSY) for the PWDs in the Food and Beverage (F&B) industry training because of the pandemic covid-19. This study, therefore, aimed to examine the relationships between the three independent variables (attitude, subjective norms, and perceived behavioural control) and the dependent variable (PWD studentsâ€™ revisit intention to attend pastry courses), using the Theory of Planned Behaviour (TPB) with gender as the moderating variable. The quantitative method was employed to investigate the relationships between the three independent variables in TPB and PWDâ€™s revisit intention. Questionnaires were used to obtain data from 146 PWD students in the Klang Valley area. This study found that all three independent variables significantly influenced PWD students’ intention to attend pastry courses at KKSY. Perceived Behavioural Control or Individual belief and control is important to PWD students and also helps teachers to predict what types of short course they most likely will attend to expand their skill acquisition. This study contributes to the body of knowledge regarding the PWD studentsâ€™ attitude, subjective norms, and perceived behavioural control to the area of hospitality education research, Furthermore, educators should give more attention and encouragement to female PWD students to increase their entrepreneurial spirit.